Long-term trends in the prevalence of patients hospitalized with ischemic stroke from 1995 to 2010 in Sweden. - Kok Wai Giang; Zacharias Mandalenakis; Susanne Nielsen; Lena Björck; Georgios Lappas; Martin Adiels; Christina Jern; Annika Rosengren (PLoS ONE, 2017)
Objective The prevalence of stroke is expected to increase partly because of prolonged life expectancy in the general population. The objective of this study was to investigate trends in the prevalence of patients hospitalized with ischemic stroke (IS) in Sweden from 1995-2010. Methods The Swedish inpatient and cause-specific death registries were used to estimate the absolute numbers and prevalence of patients who were hospitalized with and survived an IS from 1995-2010. Results The overall number of IS increased from 129,418 in 1995 to 148,778 in 2010. In 1995, the prevalence of IS was 189 patients per 10,000 population. An increase in overall prevalence was observed until 2000, and then it remained stable, followed by a decline with an annual percentage change of (APC) -0.8% (95% CI -1.0 to 0.6) and with a final prevalence of 199 patients per 10,000 population in 2010. The prevalence of IS in people aged <45 years increased from 6.4 in 1995 to 7.6 patients per 10,000 population in 2010, with an APC of 2.1% (95% CI 0.9 to 3.4) from 1995-1998 and 0.7% (95% CI 0.6-0.9) from 1998-2010. Among those aged 45-54 years, the prevalence rose through the mid to late 1990s, followed by a slight decrease (APC: -0.7%, 95% CI-1.1 to -0.4) until 2006 and then remained stable with a prevalence of 43.8 patients per 10,000 population in 2010. Among ≥85 years, there was a minor decrease (APC: -0.3%, 95% CI -0.5 to -0.1) in overall prevalence after 2002 from 1481 to 1453 patients per 10,000 population in 2010. Conclusion The overall prevalence of IS increased until 2000, but then remained stable followed by a slight decline. However, the prevalence of IS in the young increased through the study period. The absolute number of IS survivors has markedly increased, mainly because of demographic changes.